Territories of the Psyche: The Fiction of Jean Rhys - Simpson, A. author. aut Link
XIV, 168 p.
Keywords: Jean Rhys is widely credited for exposing issues of gender, nationality, race, and class in technically sophisticated, arresting narratives. Her lifelong exploration of the dynamics of the human psyche has, however, gone unrecognized. This examination places Rhys' fiction for the first time within the context of theories that reflect the interrelated perspectives of modern psychoanalysis. In clarifying accounts of many approaches that are new to literary scholars, as well as those that display the rich legacy of Freudian thought, Simpson shows that the paradigms of psychoanalysis illuminate the interpretation of Rhys' art. With insightful references to the short stories and close readings of her five novels, this study testifies to a remarkable achievement as Rhys recorded, with unflinching candor, the powerful drama of emotional life.